A dicyanobenzoquinone based cathode material for rechargeable lithium and sodium ion batteries. Issue 30 (11th July 2019) - Lyu, Hailong; Jafta, Charl J.; Popovs, Ilja; Meyer, Harry M.; Hachtel, Jordan A.; Huang, Jingsong; Sumpter, Bobby G.; Dai, Sheng; Sun, Xiao-Guang
Abstract : A novel organic cathode material has been synthesized by grafting 2, 3-dicyano- p -benzoquinone (DCBQ) onto carbon nanotubes, exhibiting not only high capacities but also remarkable long cycling stabilities in both lithium and sodium ion batteries. Abstract : Organic quinone materials offer a sustainable approach for electric energy storage, however, their intrinsic electrical insulation and dissolution into the electrolyte during cycling have hampered their wide applications. To tackle these two issues, we have synthesized a novel organic cathode material by anchoring a quinone compound, 2, 3-dicyano- p -benzoquinone (DCBQ) with a high redox potential of 3.37 V vs. Li/Li +, onto carbon nanotubes (CNTs) (CNTs-DCBQ) through a facile ''grafting to'' method. The elaborate combination of excellent electron conductivity and large surface area of CNTs and stable and reversible redox reaction of DCBQ enables CNTs-DCBQ to deliver high reversible capacities of 206.9 and 175.8 mA h g −1 at a current density of 10 mA g −1 and also remarkable capacities of 110.2 and 82.1 mA h g −1 at a higher current density of 200 mA g −1 with a capacity retention approaching 100% after 1000 cycles for lithium and sodium ion batteries, respectively.